2014
DOI: 10.1111/jfpp.12310
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Transient Heat and Mass Transfer during Deep-Fat Frying of Pantoa

Abstract: Pantoa is a traditional dairy product of the Indian subcontinent. Heat transfer in pantoa during deep-fat frying was evaluated using lumped thermal capacity model and one-dimensional transient heat conduction equation. Moisture and fat transfers were modeled using one-dimensional transient moisture diffusion equation and second order polynomial model, respectively. Lumped thermal capacity model was found to be unsuitable. As the frying temperature increased from 125C to 145C, the heat transfer coefficient obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
(53 reference statements)
6
4
0
Order By: Relevance
“…The results are also consistent with the findings of (Neethu et al, 2014). They reported that the 'k' values of Pantoa decreased from 0.23 to 1.99W/mK when fried in cooking oil at 125 to 145⁰ C at normal atmospheric pressure.…”
Section: Thermal Conductivitysupporting
confidence: 82%
See 2 more Smart Citations
“…The results are also consistent with the findings of (Neethu et al, 2014). They reported that the 'k' values of Pantoa decreased from 0.23 to 1.99W/mK when fried in cooking oil at 125 to 145⁰ C at normal atmospheric pressure.…”
Section: Thermal Conductivitysupporting
confidence: 82%
“…These results are consistent with frying of similar indigenous dairy products (Neethu et al, 2014) and may be attributed to the effect of crust formation and its effect on thermal diffusivity.…”
Section: Thermal Diffusivitysupporting
confidence: 80%
See 1 more Smart Citation
“…So far, numerous research works relating to deep-fat frying modelling have been described in different fried foods [12][13][14]. A variety of mathematical models for mass transfer of deep-fat frying are proposed; for example, the first-order kinetic model and the second-order polynomial model for fat absorption [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The changes in porosity of pantoa , at different stages of frying, was measured by compressing the samples in a texture analyzer (model TA‐XT Plus, Stable Micro Systems, Godalming, UK) equipped with 50 kg load cell, which allowed near complete removal of voids (Neethu et al . ). Finely‐ground mass of pantoa was loaded into a cylinder of 50.34 mm diameter and 100 mm height, and it was compressed using P/50 platen.…”
Section: Methodsmentioning
confidence: 97%